Pengaruh Variasi Debit dan Jumlah Elektroda Terhadap Penurunan COD dan Produksi Listrik Dalam Reaktor Microbial Fuel Cells (MFCs) Studi Kasus: Air Limbah Rumah Potong Hewan (RPH) Kota Salatiga - Septyana, Ian; Ardhianto Ganjar Samudro, Rachmad (DIPOIPTEKS: Jurnal Ilmiah Mahasiswa Undip, 2013)
This research is a wastewater treatment miniature using microbial fuel cells (MFCs) reactor. The purpose of this study to find the optimum flowrate and total electrode to decrease concentration of COD and electricity production in microbial fuel cells (MFCs) reactor can optimum too. The best reactor of this research is reactor 1 where using flowrate 0,1 l/h and total electrode 3. In reactor 1 show that effluent concentration is 56,67 mg/l while for electricity production is 550 mV.Keywords: Microbial fuel cells, flowrate, total electrode, COD, electricity production